Reduction in thermal sensitivity to cold during exercise and post-exercise recovery - Ouzzahra, Y.; Havenith, G.; Redortier, B.; Voelcker, T. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
A low skin temperature (Tsk) at the onset of exercise has been shown to improve performance (Schlader et al., 2011). Preexercise skin cooling is however limited by cold and uncomfortable perceptions resulting from a reduced Tsk. According to the concept of thermal alliesthesia (Cabanac, 1972), light exercise during skin cooling may improve thermal comfort associated with a low Tsk. Therefore, the aim of the present study was to compare thermal sensation and thermal comfort before, during, and after exercise, while cooling the skin in one body segment. Methods: Using a customised liquid cooling garment, the whole chest of eight male participants (22.0 ± 3.6 y; 181.8 ± 2.3 cm; 78.3 ± 5.7 kg) was continuously cooled during three consecutive conditions: 30 min rest, 15 min exercise (cycling at 30% VO2max) and 15 min post-exercise recovery. Thermal sensation from 0 ("neutral) to -10 ("extremely cold") and thermal comfort from +5 (very comfortable) to -5 (very uncomfortable) were scored at 5 min intervals. Core temperature (Tc) and chest Tsk (4 sites) were recorded throughout the experiment. Results: Cooling caused a chest mean Tsk decrease from 33.0 ± 0.6°C to 28.1 ± 0.9°C in the resting period, resulting in a local thermal sensation of -6.9 ± 1.6 and a local thermal comfort of -3.4 ± 1.1. Despite a further decrease in Tsk to 27.8 ± 0.9°C during the exercise period, thermal sensation and thermal comfort both increased, respectively to -1.8 ± 1.8 (p<0.05) and 1.0 ± 2.1 (p<0.05). This was accompanied by a minimal increase in Tc (0.1 ± 0.1°C). During the recovery period, Tsk further decreased to 26.6 ± 1.0°C, while thermal sensation and thermal comfort decreased to -4.9 ± 1.1 (p<0.05) and -2.0 ± 0.9 (p<0.05), respectively. Discussion: The improvement in thermal comfort is in line with the concept of thermal alliesthesia. However, the mechanisms behind the decrease in thermal cold sensation despite a lower Tsk remain unclear, but may be related to the activation of stress-induced analgesia during exercise (Koltyn, 2000). The present results suggest the possibility of reducing discomfort and cold sensation by the incorporation of light exercise in pre-performance cooling strategies.